Knee Extensor Power Relates to Mobility Performance in People With Knee Osteoarthritis: Cross-Sectional Analysis. Issue 7 (1st July 2015) - Accettura, Angela J.; Brenneman, Elora C.; Stratford, Paul W.; Maly, Monica R.
Abstract : Background: Quadriceps femoris muscle strengthening is a common rehabilitation exercise for knee osteoarthritis (OA). More information is needed to determine whether targeting muscle power is a useful adjunct to strengthening for people with knee OA. Objective: The purpose of this study was to identify the predictive ability of knee extensor strength and knee extensor power in the performance of physical tasks in adults with knee OA. Design: This study used a cross-sectional design. Methods: Fifty-five participants with clinical knee OA were included (43 women; mean [SD] age=60.9 [6.9] years). Dependent variables were: timed stair ascent, timed stair descent, and the Six-Minute Walk Test (6MWT). Independent variables were: peak knee extensor strength and mean peak knee extensor power. Covariates were: age, body mass index, and self-efficacy. Multiple regression analyses were run for each dependent variable with just covariates, then a second model including strength, and then a third model including power. The R 2 values were compared between models. Results: Power explained greater variance than strength in all models. Over and above the covariates, power explained an additional 6% of the variance in the 6MWT, increasing the R 2 value from .33 to .39; 8% in the stair ascent test, increasing the R 2 value from .52 to .60; and 3% in the stair descent test, increasing the R 2 value from .44 to .47. Limitations: The sample demonstrated very good mobility and muscle function scores and may not be indicative of those with severe knee OA. Conclusions: In adults with knee OA, knee extensor power was a stronger determinant of walking and stair performance when compared with knee extensor strength. Clinicians should consider these results when advising patients on exercise to maintain or improve mobility.